Analisis Yuridis tentang Perlindungan Hak Merek dalam Era Digital: Studi Kasus tentang Pelanggaran Hak Merek di Platform Marketplace Shopee - Syaifulloh, Syahrul Akbar (Proceedings Series on Social Sciences & Humanities, 2024)
Brand rights are an important asset for a company because a brand reflects the identity and reputation of a product or service in the eyes of consumers. Protection of brand rights not only protects brand owners from unauthorized use by other parties but also protects consumers from counterfeit products that can harm them financially and health. The purpose of this writing is to find out how the Juridical Analysis of Brand Rights Protection in the Digital Era: Case Study of Brand Rights Violations on the Shopee Marketplace Platform. Normative juridical research methods. The research results show that brand rights protection in the digital era requires a comprehensive and adaptive approach to technological developments. Shopee as one of the main marketplace platforms in Indonesia has made various efforts to protect brand rights, but there are still challenges that must be overcome. Through increased regulation, consumer education, and the use of advanced technology, brand rights protection can be improved to support a healthy and fair digital trade ecosystem.